Education of Heart Attack Prevention and Heart Disease Risk Stratification in Banyumas Regency - Supadi, Supadi; Prasetyo, Herry; Subandiyo, Subandiyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Every year more than 36 million people die from non-communicable diseases (NCD), which is about 63% of deaths caused by NCDs. Globally, PTM which is the number one cause of death every year is cardiovascular disease that can occur before the age of 60 years, and 90% of these premature deaths occur in low and middle income countries (Kemenkes RI, 2014). In Central Java Province, based on reports from hospitals, the highest cases of coronary heart disease were in the city of Semarang, amounting to 4,784 cases (26.00%) compared to the total number of coronary heart disease cases in other districts/cities in Central Java. When viewed based on the total number of other PTM cases in Klaten Regency, it was 3.82%. Meanwhile, the second highest case was Banyumas Regency, which was 2,004 cases (10.89%) and when compared to the total number of other PTMs in Banyumas Regency, it was 9.87%. The fewest cases were found in Tegal Regency, namely 2 cases (0.01%) (Health Profile of Central Java Province, 2014). This study aims to determine the effect of education on heart prevention efforts on the stratification of heart disease. This type of research is quasi-experimental with pre and post test designs with controls. The number of samples is 40 respondents, 20 samples as the intervention group and 20 respondents as the control group. The results of the dependent t test analysis showed that there was an effect of education on prevention of heart disease on the reduction of heart disease stratification with p value: 0.00. There is an effect of education on prevention of heart disease on reducing the stratification of heart disease.